Fit for purpose? A cross-sectional study to evaluate the acceptability and usability of HeadUp, a novel neck support collar for neurological neck weakness. Issue 1 (2nd January 2021) - Sproson, Lise; Lanfranchi, Vitaveska; Collins, Alexis; Chhetri, Suresh K.; Daly, Niamh; Ennis, Michelle; Glennon, Lucie; Gorrie, George; Jay, Emily; Marsden, Rachael; McCarthy, Avril D.; Pryde, Liz; et al.
Abstract: The HeadUp collar (previously known as the Sheffield Support Snood) provides support for neck weakness caused by amyotrophic lateral sclerosis (ALS) and has shown to be superior to alternative options in a small cohort of patients from one single center. Here we report the assessment of the HeadUp collar in a larger cohort of patients, exploring the use in other neurological conditions and expanding to other centers across the UK and Ireland. An interventional cross-sectional study design was implemented to investigate the usability and acceptability of the HeadUp collar. A total of 139 patients were recruited for the study, 117 patients had a diagnosis of ALS and 22 patients presented with neck weakness due to other neurological conditions. Participants were assessed at baseline, fitted a HeadUp collar and followed-up one month later. The performance of the HeadUp collar was rated favorably compared to previously worn collars in terms of the ability to eat, drink and swallow. Findings suggest that the collar also permitted a more acceptable range of head movements whilst maintaining a good level of support. We conclude that the HeadUp collar is a suitable option for patients with neck weakness due to ALS and other neurological conditions.